PERAN PEREMPUAN DALAM INDUSTRI RUMAHAN KERAJINAN MEMBUAT WADAH TELURUNTUK ACARA AQIQAH DESA BANJARREJO KECAMATAN BATANGHARI LAMPUNG TIMUR - Novi Riani (Center of Gender Studies and Child of State Islamic Institute of Metro, 2019)
Abstract : Craft home industry activities making egg containers for the aqiqahevent prove that women can not only play a role in making a living for families but also can create jobs, especially for housewives.The objectives in this research are to find out the role of women in the form of involvement in the handicraft home industry to make egg containers for the aqiqah event.To find out the role of women in the form of outpouring of work in the home-based handicraft industry making egg containers for the aqiqah event. In order to know the role of women in-depth in the home-based industry of handicraft making egg containers, this study uses a qualitative approach. This type of research is a type of field research and is descriptive. Based on the results of the discussion, it can be said that the participation of women in the economic world must be admitted inevitably, despite the fact that there are differences in the emergence of work activities between men and women. It is known that women who support the household economy with the aim of helping their husbands participate in working for a living. The role of women who work for a living to help their household economy, these women have contributed their time and energy to generate wages from the work they do. Women or housewives who work take part in earning an average income due to economic factors. Suggestions that can be given in this study are as follows to women who participated in the work, one of them worked in the home industry in order to improve their skills and be diligent in what they did, so that in the future it is possible to run their own businesses.To the home industry entrepreneurs to pay attention and develop again the quality of the business they run, both in terms of production, packaging and marketing.